PENAMBAHAN LIMBAH SPONS SANDAL EVA TERHADAP KARAKTERISTIK ASPAL MODIFIKASI PG 70 PADA CAMPURAN ASPAL BETON - Raihan Bryne Firdaus Al Machrus; Rizkiardi, Aditya; Hartatik, Nurani; Ervitasari, Siska Yovina; Punarta, I Gede Agus (Jurnal Teknik Sipil dan Arsitektur, 2025)
In Indonesia, waste from home industries is still a major challenge in sustainable environmental management efforts. One type of waste that is often overlooked is Ethylene Vinyl Acetate (EVA)-based sandal sponge waste. This waste is generally disposed of without further utilization, thus potentially polluting the surrounding environment. This research aims to utilize EVA waste as an additive in PG 70 modified asphalt mixture in the asphalt concrete layer, which is a road pavement layer that directly bears the traffic load and must be able to withstand vertical pressure, shear force, deformation, and temperature fluctuations. EVA waste was processed through washing, shredding, and drying before being mixed into the asphalt using the wet mixing method. A series of laboratory tests were conducted to assess the effect of EVA addition on the physical characteristics of asphalt, including penetration, flash point, ductility, specific gravity, and softening point tests. The results showed that the addition of EVA waste tended to increase the flash point and softening point, but decreased the penetration, ductility, and specific gravity values. All test parameters are still within the limits required by the General Specifications of Bina Marga 2018 (Revision 2). These findings prove that EVA waste has potential as an additive that not only improves asphalt performance, but also supports more environmentally friendly and sustainable waste management solutions. Keyword : PG 70 asphalt, EVA waste, asphalt concrete, physical characteristics, asphalt modification.